Neutrophilic inflammation promotes SARS-CoV-2 infectivity and augments the inflammatory responses in airway epithelial cells - Calvert, Ben A.; Quiroz, Erik J.; Lorenzana, Zareeb; Doan, Ngan; Kim, Seongjae; Senger, Christiana N.; Anders, Jeffrey J.; Wallace, Wiliam D.; Salomon, Matthew P.; Henley, Jill; Ryan, Amy L. (Frontiers in Immunology, 2023)
In response to viral infection neutrophils release inflammatory mediators as part of the innate immune response and contribute to pathogen clearance through virus internalization, killing and the release of cytokines and chemokines. It remains uncertain how critical the neutrophil stage of the response is in anti-viral immunity and to what extent this contributes to the cytokine response of the airways in COVID-19. Furthermore, many COVID-19 pre-existing co-morbidities are associated with chronic airway neutrophilia. To evaluate the role of neutrophils in the airway’s response to SARS-CoV-2 we have developed a co-culture model to study infection, combining primary human neutrophils and differentiated airway epithelial cells. ACE2, the key receptor for binding the S-protein of SARS-CoV-2, was predominantly expressed in submucosal glands and in ciliated cells in the proximal airways. Surprisingly, infiltrating leukocytes also had strong expression of ACE2, specifically co-localized in neutrophils expressing neutrophil elastase and CD15. In the presence of neutrophils, a heightened inflammatory response to SARS-CoV-2 infection was observed including an impairment in epithelial barrier integrity and upregulation of secreted pro-inflammatory cytokines, including IFNγ, IL-1β, IL-6 and TNFα after SARS-CoV-2 infection for 4 hours. In the physical absence of neutrophils, the pro-inflammatory cytokines also impaired barrier integrity and increased viral load in epithelial cell monocultures. Overall, this study demonstrates that neutrophils significantly impact the consequences of SARS-CoV-2 airway infection, leading to a hyper-inflammatory response, highlighting the need to study SARS-CoV-2 infection in more complex, tissue level models to fully understand the mechanisms driving the severe inflammatory response and the long-term consequences of infection.